E-Marketing of Village Tourism Development Strategy (Case Study in the Tourist Village Puncak Sosok) - Ramadhani, Ramadhani (Journal of Robotics and Control (JRC), 2021)
Attractions peak figure is one of the national tourism objects located in the village Bawuran, District Pleret, Bantul which have tourism potential is extraordinary for the future. The purpose of this study is to describe the strategy of the development of the tourism village of Puncak Sosok. The approach used in this research is descriptive qualitative data collection methods such as interviews with informants interested and involved in the direct management attractions peak figure. Analysis of data obtained through data collection, data verification, data presentation, and conclusion. The results showed that the peak tourism village development strategy figure through the potential of natural resources, marketing strategy, and human resource management is already well underway with a high enough public participation in all stages of management. Therefore, electronic marketing (e-marketing) is the right tourism development strategy in Puncak Sosok.